Evaluation of smoke gas toxicity and smoke density of bus interior materials. (4th August 2022) - Sandinge, Anna; Fredriksson, Henrik; Blomqvist, Per
Abstract: Materials used for interior parts in buses are today fire classified according to UNECE Regulation 118, evaluating the horizontal and vertical burning rates and the melting behaviour. However, in recent accidents, the smoke has been identified as the critical parameter for deaths. An evaluation has been made of six materials used as interior parts in busses and is presented in this paper. Fire testing was conducted according to UNECE R 118 and smoke production including smoke gas toxicity was further evaluated with the smoke chamber test, EN ISO 5659‐2 and EN 17084. All six tested materials fulfilled the requirements of UNECE R 118; however, most materials showed fire properties which are not desirable, such as dark smoke and melting of large burning pieces. The tests with the smoke chamber showed that all materials gave a very high smoke production, in fact a smoke density value of the highest possible for the equipment to measure. This occurred only after a few minutes of test time. Thus, it can be concluded that this high smoke production will, in case of fire in a bus, reduce the visibility, and limit the ability of the passengers to safely evacuate. In addition, several toxic gases were detected in the smoke, both irritants and suffocating gases.